Ultrasound-guided supraclavicular brachial plexus block as an additive to sevoflurane anesthesia in pediatrics undergoing brachiobasilic arteriovenous fistula operation: randomized controlled clinical trial - Saeid Elsawy; Esraa Fathy; Ahmed Elbadawy; Ashraf Elnaggar; Ahmed Fathy Abdelatif; Hany Elmorabaa; Rasha Hamed (BMC Anesthesiology)
Abstract Background Renal disease is a significant cause of morbidity and mortality in children and is uniquely challenging in the anesthetic management of pediatric patients. Perioperative pain management is a core component in the anesthetic plan. Pediatric regional anesthesia is one of the most valuable and safe tools to treat perioperative pain. Methods Sixty pediatric patients with chronic kidney disease scheduled for upper limb superficialization of brachiobasilic arteriovenous fistula to facilitate hemodialysis completed the study. Patients were randomly allocated into two groups; the block group received combined general anesthesia plus ultrasound-guided supraclavicular block, and the control group received general anesthesia only. Results The block group recorded a significantly lower fistula maturation duration, more dilatation in basilic vein diameter, lower primary failure rate, postoperative VAS scores, anesthesia consumption, better RASS scores and longer analgesia duration. Moreover, the block group showed more stable hemodynamics with less reduction in MAP than the control group. Conclusion Ultrasound-guided supraclavicular brachial plexus block is a safe and feasible adjuvant to general anesthesia that could reduce brachiobasilic AVF maturation time, primary failure rate, control perioperative operative pain and improve the quality of anesthesia recovery by reducing emergence agitation and minimizing sevoflurane anesthesia consumption in pediatric patients with end-stage renal disease. Trial registration The study was registered on clinical trial registration (NCT05580094) in October 2022.